A reverse engineering approach for low environmental impact earth stabilization technique. Issue 4 (November 2020) - Cicek, B; Martins, N P; Brumaud, C; Habert, G; Plötze, M
Abstract: The major drawbacks of earth such as low water stability and moderate strength have led mankind to stabilize the earth. It has been developed as a vernacular technique in different civilizations. Since then, the focus was mainly on gypsum, lime, or pozzolan stabilization. Recently, cement has become one of the commonly used additives in earth stabilization, which consequently reduce the environmental advantage of earth. This paper deals with a reverse engineering approach for low environmental impact earth stabilization technique, aiming the replacement of cement in earth stabilization. Various earth-mixtures were done to investigate the performance of this technique. Water contact behaviour and compressive strength of the stabilized earth specimens was determined. Moreover, the characterization of the stabilization effect has been performed through X-ray powder diffraction patterns (XRD) and clearly identify the production of ettringite using very low CO2 intensive raw materials. Furthermore, the carbon footprint of the stabilized earth-mix has been determined with the help of LCA (life cycle assessment) calculation. The laboratory analyses on this mix-design have proven a high water-resistance and the results show a remarkable increase in compressive strength. Finally, these results open a new avenue for earth stabilization and secure the implementation of this material in the conventional construction industry.